DIFFERENCES IN ANXIETY AND INSOMNIA LEVELS BETWEEN OBESE AND NON-OBESE STUDENTS CLASS OF 2016 OF THE FACULTY OF MEDICINE, DIPONEGORO UNIVERSITY - Sri Mulyasari; Widodo Sarjana; Titis Hadiati (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Anxiety and insomnia can be experienced by anyone, including students, both obese and non-obese. Many pressures and problems experienced by obesity and non-obesity students will cause discomfort and have an impact on mental health problems such as anxiety which can develop insomnia. Objective: To determine differences in levels of anxiety and insomnia among college obesity and non-obesity students, faculty of medicine. Methods: This study is an observational analytic study with cross-sectional approach. The sample is 122 people, consisting of 21 respondents obesity and 101 respondents of non-obese who are students of the Faculty of Medicine Batch 2016 Universitas Diponegoro. Sampling with a total sampling method. Measured respondents ' level of anxiety using a questionnaire Zhung Self-rating Anxiety Scale and the level of insomnia using a questionnaire Insomnia SeverityIndex. The test used is Chi-square. Results: The research results showed that anxiety in obesity 1.6% and non-obesity of 3.3%. While insomnia in obesity of 8.2% and the non-obesity of 28.7%. Based on the results of statistical tests show there is no significant difference in anxiety levels between obese and non-obese (p=275) and there is no significant difference in the level of insomnia among obese and non-obese (p=0,475). Conclusions: There is no significant difference in terms of the level of anxiety and insomnia between obesity and non-obesity.Keywords: Anxiety, insomnia, obesity, non-obesity